Targeting the Wnt/β-catenin pathway: veratramine mitigates MNNG-induced gastric precancerous lesions - Pan Zhang; Xuelin Sun; Longteng Liu; Yatong Zhang; Jiaqi Bo; Wenli Huang; Yifan Na; Jingyi Zhang; Xiaoyun Qin; Qingfeng Luo (Molecular and Cellular Biochemistry, 2026)

Ultrasensitive and selective detection of metronidazole residues in milk powder using a novel 3D MOF fluorescent sensor - Xuanqi Zhang; Guiling Gao; Xiaoyong Lai; Qin Hou; Yi Li; Zhiyong Teng; Xiaozhong Wang; Xiao Zhang; Qingfeng Yang (Food Chemistry, 2026)

Research on vertical ecological compensation mechanism based on ecosystem services supply-demand balance—A case study of the Nine Plateau Lakes in Yunnan Province - Jianjun Sheng; Qingfeng Xiao; Zhanpeng Du; Qin Zhang; Yan liu; Yinglan Xue (Environment, Development and Sustainability, 2026)

Comprehensive evaluation of reheating methods on pork meatballs: Focusing on physicochemical properties, flavor profiles and their impact on eating quality - Qin Hou; Tianyi Gao; Jiaxin Wu; Yao Li; Qingfeng Ge; Zhuangli Kang (International Journal of Gastronomy and Food Science, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Conservation and divergence of OsGSTU9 and OsGSTU19 in cadmium detoxification and accumulation in rice - Xuan Chen; Wei Jiang; Di Chang; Qingfeng Zheng; Chunmeng Zhu; Li Hao; Fanrong Zeng; Zhong-Hua Chen; Guang Chen; Yuan Qin; Fenglin Deng (Journal of Hazardous Materials, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Copper stearate-coated DAP-4 core–shell composites for enhanced safety and thermal decomposition performance - Xueli Zhang; Erhai An; Guangwei Xiao; Qingfeng Qin; Yingxin Tan; Peng Deng; Xiong Cao (Fuel, 2024)

Study on Impact Tendency and Damage Characteristics of Rock-Like Materials Based on Acoustic and Thermal Responses - Shoujian Peng; Yan Yang; Qingfeng Xu; Jiang Xu; Chaolong Qin; Xiaoli Nong (Rock Mechanics and Rock Engineering, 2024)

Cr(VI) behaves differently than Cr(III) in the uptake, translocation and detoxification in rice roots - Adeel Riaz; Yuan Qin; Qingfeng Zheng; Xuan Chen; Wei Jiang; Bisma Riaz; Nayun Xiao; Xiaojian Wu; Xianjin Qiu; Jianlong Xu; Guang Chen; Zhong-Hua Chen; et al. (Science of The Total Environment, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Recent progress in carbonaceous materials for the hydrogen cycle: Electrolytic water splitting, hydrogen storage and fuel cells - Guanghui Xia; Habibullah; Qingfeng Xie; Qin Huang; Meitong Ye; Bingshou Gong; Rui Du; Yao Wang; Yigang Yan; Yungui Chen; Chaoling Wu (Chemical Engineering Journal, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Geochemistry of rare earth elements and yttrium in Late Permian coals from the Zhongliangshan coalfield, southwestern China - Qingfeng Lu; Shenjun Qin; Hongyang Bai; Wenfeng Wang; De’e Qi; Xin He; Bofei Zhang (Frontiers of Earth Science, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Geochemistry of Late Permian coals from the Moxinpo mine, Chongqing, Southwestern China: Emphasis on petrology, minerals, and organic matter - Qingfeng Lu; Shenjun Qin; Wenfeng Wang; Kang Gao; Jingkai Xing (Applied Geochemistry, 2023)

Geochemistry of Late Permian coals from the Yueliangtian coal deposit, Guizhou: Evidence of sediment source and evaluation on critical elements - Qingfeng Lu; Shenjun Qin; Wenfeng Wang; Qian Wang; Shuai Kang (Science of The Total Environment, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

Targeted disruption of tyrosinase causes melanin reduction in Carassius auratus cuvieri and its hybrid progeny - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Jia Song; Junmei Liu; Wuhui Li; Yuqin Shu; Min Tao; Chun Zhang; Qinbo Qin; Jing Wang; Shaojun Liu (Science China Life Sciences, 2019)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

An improved reverse transcription loop-mediated isothermal amplification assay for sensitive and specific detection of Newcastle disease virus - Qiang Li; Chunyi Xue; Jianping Qin; Qingfeng Zhou; Feng Chen; Yingzuo Bi; Yongchang Cao (Archives of Virology, 2009)